IMPLEMENTASI LOAD BALANCING PADA JARINGAN MENGGUNAKAN ROUTER MIKROTIK DI KANTOR DESA JUM’AT - Hendri Alamsyah; Putra Dwi Nurdiyanto; Yoli Andi Rozzi (Jusikom : Jurnal Sistem Komputer Musirawas, 2026)
The development of information technology requires government agencies to have a stable and efficient internet network. The Jum'at Village Office faced traffic congestion on a single ISP path. This study applies the Per Connection Classifier (PCC) Load Balancing method on a MikroTik Router to improve network stability and efficiency. Using an experimental quantitative method, the research compared Traffic Graph before and after implementation, sticky connection testing, and traffic distribution. Results show PCC reduced traffic congestion, improved download speed from 1.1 Mbps to 4.2 Mbps and upload from 2.3 Mbps to 8.5 Mbps. Traffic was balanced: 3 PCs used ISP 1 (Iconnet) and 2 PCs used ISP 2 (Indosat). PCC-based Load Balancing on a MikroTik Router effectively improved speed, reduced traffic load, and enhanced routing efficiency.